Multilevel Regulation of NF‐κB Signaling by NSD2 Suppresses Kras‐Driven Pancreatic Tumorigenesis - Wenxin Feng; Ningning Niu; Ping Lu; Zhuo Chen; Hanyu Rao; Wei Zhang; Chunxiao Ma; Changwei Liu; Yue Xu; Wei‐Qiang Gao; Jing Xue; Li Li (Advanced Science, 2024)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a clinically challenging cancer with a dismal overall prognosis. NSD2 is an H3K36‐specific di‐methyltransferase that has been reported to play a crucial role in promoting tumorigenesis. Here, the study demonstrates that NSD2 acts as a putative tumor suppressor in Kras‐driven pancreatic tumorigenesis. NSD2 restrains the mice from inflammation and Kras‐induced ductal metaplasia, while NSD2 loss facilitates pancreatic tumorigenesis. Mechanistically, NSD2‐mediated H3K36me2 promotes the expression of IκBα, which inhibits the phosphorylation of p65 and NF‐κB nuclear translocation. More importantly, NSD2 interacts with the DNA binding domain of p65, attenuating NF‐κB transcriptional activity. Furthermore, inhibition of NF‐κB signaling relieves the symptoms of Nsd2‐deficient mice and sensitizes Nsd2‐null PDAC to gemcitabine. Clinically, NSD2 expression decreased in PDAC patients and negatively correlated to nuclear p65 expression. Together, the study reveals the important tumor suppressor role of NSD2 and multiple mechanisms by which NSD2 suppresses both p65 phosphorylation and downstream transcriptional activity during pancreatic tumorigenesis. This study opens therapeutic opportunities for PDAC patients with NSD2 low/loss by combined treatment with gemcitabine and NF‐κBi.